Transcriptional dynamics and epigenetic regulation of E and ID protein encoding genes during human T cell development - Roels, Juliette; Van Hulle, Jolien; Lavaert, Marieke; Kuchmiy, Anna; Strubbe, Steven; Putteman, Tom; Vandekerckhove, Bart; Leclercq, Georges; Van Nieuwerburgh, Filip; Boehme, Lena; Taghon, Tom (Frontiers in Immunology, 2022)
T cells are generated from hematopoietic stem cells through a highly organized developmental process, in which stage-specific molecular events drive maturation towards αβ and γδ T cells. Although many of the mechanisms that control αβ- and γδ-lineage differentiation are shared between human and mouse, important differences have also been observed. Here, we studied the regulatory dynamics of the E and ID protein encoding genes during pediatric human T cell development by evaluating changes in chromatin accessibility, histone modifications and bulk and single cell gene expression. We profiled patterns of ID/E protein activity and identified up- and downstream regulators and targets, respectively. In addition, we compared transcription of E and ID protein encoding genes in human versus mouse to predict both shared and unique activities in these species, and in prenatal versus pediatric human T cell differentiation to identify regulatory changes during development. This analysis showed a putative involvement of TCF3/E2A in the development of γδ T cells. In contrast, in αβ T cell precursors a pivotal pre-TCR-driven population with high ID gene expression and low predicted E protein activity was identified. Finally, in prenatal but not postnatal thymocytes, high HEB/TCF12 levels were found to counteract high ID levels to sustain thymic development. In summary, we uncovered novel insights in the regulation of E and ID proteins on a cross-species and cross-developmental level.